Measurement of total energy expenditure by the doubly labelled water method in professional soccer players - Ebine, N.; Rafamantanantsoa, H. H.; Nayuki, Y.; Yamanaka, K.; Tashima, K.; Ono, T.; Saitoh, S.; Jones, P. J. (Journal of Sports Sciences, 2002)
To determine the daily energy requirements of professional soccer players during a competitive season, we measured total energy expenditure in seven players (age 22.1+/-1.9 years, height 1.75+/-0.05 m, mass 69.8+/-4.7 kg; mean +/- s) using the doubly labelled water method. Energy intake was simultaneously estimated from 7 day self-report dietary records. Mean total energy expenditure and energy intake were 14.8+/-1.7 MJ x day(-1) (3532+/-408 kcal x day(-1)) and 13.0+/-2.4 MJ x day(-1) (3113+/-581 kcal x day(-1)), respectively. Although there was a significant difference between total energy expenditure and energy intake (P < 0.01), there was a strong relationship between the two (r= 0.893, P< 0.01). Basal metabolic rate and recommended energy allowance calculated from the Recommended Dietary Allowances for the Japanese were 7.0+/-0.3 MJ x day(-1) (1683+/-81 kcal x day(-1)) and 15.6+/-0.8 MJ x day(-1) (3739+/-180 kcal x day(-1)), respectively. A physical activity level (total energy expenditure/ basal metabolic rate) of 2.11+/-0.30 indicated that, during the competitive season, professional soccer players undertake much routine physical activity, similar to that of competitive athletes during moderate training. Energy intake estimated using dietary records was under-reported, suggesting that its calculation from these data does not predict energy expenditure in soccer players.